What influences Australian secondary schools in their efforts to prevent and intervene in cyberbullying?. Issue 3 (2nd July 2020) - Pennell, Donna; Campbell, Marilyn; Tangen, Donna
ABSTRACT: Background: Cyberbullying is a significant problem for young people and secondary schools are the main institutions expected to address it. School anti-bullying measures have only modestly reduced the problem to date. Purpose: This study aimed to examine the perspectives of members within the school community regarding their actions to reduce cyberbullying. Method: School stakeholders were recruited from two large independent high schools in Australia. Overall, four school leaders, two key personnel with roles in cyberbullying prevention, and two parents participated in semi-structured interviews, while two groups of Year 9 teachers, and four groups of Year 9 students (aged 13–15 years) participated in focus groups. Interview and focus group protocols were developed to gather views about prevention and intervention measures for cyberbullying in the stakeholders' schools. Copies of anti-cyberbullying policies and documents were also collected for review. Analysis: A thematic content analysis was conducted on 14 stakeholder transcripts from interviews and focus groups, and school policy documents were reviewed for anti-bullying components. The distal systems of a social-ecological framework were used to frame a wider view of school efforts to prevent and intervene in cyberbullying. Findings: The content analysis and review showed that school actions were reflective of evidence-based best practice. However, despite actions towards making students safe from cyberbullying, stakeholders were left questioning why these incidents were still observed. The analysis revealed that the continued presence of cyberbullying was not simply attributable to ineffective school practices, but rather from societal influences. Three macrosystem themes were identified from the data: the culture of technology; the legal framework; and the media portrayal of cyberbullying. These macrosystem influences could be seen impacting four school exosystems (i.e. communities of school practice): the parent community, the organisational community, the support and advice community, and commercial communities of schools. Conclusion: The macrosystems and exosystems of schools are influencing school actions, with implications for the reduction of student cyberbullying.